Legal Clinics in Continental Western Europe: The Approach of the Utrecht Legal Clinic on Conflict, Human Rights, and International Justice (2010)
I would like to thank Rick Wilson, Elizabeth Andersen, and the American Society of International Law for giving me the opportunity to talk about something on which Dr. Leo Zwaak and I have spent most of our time since my appointment as the Chair of International Criminal Law and Procedure at the University of Utrecht: the newly established Utrecht Law Faculty Clinical Programme on Conflict, Human Rights and International Justice (hereinafter the Utrecht Legal Clinic). In continental western Europe, legal education has been traditionally divided into two different stages. Students were first provided with a basic theoretical framework during their bachelor-in-law education. They were subsequently given an opportunity to apply such a framework in actual cases through traditional apprenticeships. This was accompanied with the institutionalization at the bachelor’s level of the so-called magister or ex catedra lessons, which are based on a teaching technique that lacks interaction between a law professor’s explanation of general principles of law and students listening to the professor’s explanations. As a result, a gap was created between law schools, where students were taught the core legal principles of a plurality of legal disciplines, and judicial institutions, law firms, and nongovernmental organizations, where apprenticeships were subsequently carried out. This, in turn, meant that for several years law students were not exposed to the problems caused by the application in real life of the principles that they learned at the university. Nevertheless, in the last decade, we have experienced in continental western Europe a slow but steady movement toward other forms of legal education which combine theoretical teaching of basic legal principles with awareness of the main problems posed by the actual application of such principles in real cases